2020
DOI: 10.1177/1066480720932835
|View full text |Cite
|
Sign up to set email alerts
|

Family Emotional Security and Problem Drinking Among Young Adult Males in Romantic Relationships

Abstract: The current study evaluated the unique associations between three dimensions of emotional security in the family system (security, disengagement, and preoccupation) and problem drinking among romantically partnered males aged 18–30 years. The sample consisted of 49 males who were recruited with their partners as part of a broader study on substance behaviors. It was hypothesized that security in the family system (i.e., secure appraisals) would be negatively related to problematic drinking, whereas insecure ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We found that disengagement from the family system (but not preoccupation) was related both to justification of violence and CPV against the mother. These results are consistent with a multitude of studies that establish a relationship between feeling disengaged in the family and a worse adaptation of the child and more problematic behaviors (Barringer & Papp, 2020). Therefore, these results are consistent with the EST because, as Davies and Cummings (1994) proposed, children achieve emotional security within the family when they establish strong bonds but if this does not occur, it leads to the development of strategies for coping with stress that implies children’s poorer adjustment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that disengagement from the family system (but not preoccupation) was related both to justification of violence and CPV against the mother. These results are consistent with a multitude of studies that establish a relationship between feeling disengaged in the family and a worse adaptation of the child and more problematic behaviors (Barringer & Papp, 2020). Therefore, these results are consistent with the EST because, as Davies and Cummings (1994) proposed, children achieve emotional security within the family when they establish strong bonds but if this does not occur, it leads to the development of strategies for coping with stress that implies children’s poorer adjustment.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, as a large previous body of research has confirmed, children who employ such disengagement or preoccupation strategies in order to maintain emotional security will be at increased risk of developing psychological and social difficulties. Studies have found relationships between disengagement/preoccupation strategies and the likelihood of presenting school problems, psychological distress, addictive behaviors, substance abuse, or even suicidal ideation (Barringer & Papp, 2020; Cantón-Cortés et al, 2020; Coe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Articles included in the disorders secondary theme recommend that our conceptualization of a disorder in the identified client or family recognize and incorporate a cybernetic etymology, development and maintenance of the identified disorder. Articles consistent with this secondary theme applied this cybernetic awareness to issues in couples and family systems work (Asfaw et al, 2020), addiction related disorders (Barringer & Papp, 2020; Belmontes, 2018; Day, 2017; Jankowski & Hooper, 2014), trauma and grief related disorders (Dickens, 2014; Katafiasz, 2020; Muselman & Wiggins, 2012; Overton & Cottone, 2016; Southern & Sullivan, 2021), self-harm and suicidality (Buser et al, 2014), physical disabilities, somatoform disorders, and illness (Feather et al, 2018; Sperry, 2012; Taylor & Lewis, 2018), and nonspecific pathology (Hooper & Newman, 2011; Zagefka et al, 2021).…”
Section: Resultsmentioning
confidence: 99%